Does your SOA achieve agility? : SOA actualization enterprise agility. - Schneider, Jeff (SOA webservices journal.)
Agility seems to be the buzzword du jour. There are "agile enterprises," "agile manifestos," "agile programmers," and "agile architectures." Slap "agile" in front of just about anything and marketers believe it will sell better. Yet, one of the primary goals of using service-based architectures was to create "agile systems." This begs the question, was it just marketing or is there something to it?